Analyzing the Feasibility of Photovoltaic Solar Systems in the Parking Area of Universitas Multimedia Nusantara: A PVSyst Simulation-based Investigation - Vanesa Lorent; Agie Maliki Akbar; Fahmy Rinanda Saputri (Universitas Islam Raden Rahmat, Malang, 2024)
The article explores the feasibility and economic viability of installing a solar power generation system at the rear parking area of Universitas Multimedia Nusantara (UMN). Utilizing PVSyst simulation, the study demonstrates that the proposed system can generate 224 MWh of electricity annually, meeting 20% of the energy needs for nearby buildings A and D. Despite requiring an initial investment of Rp. 781,883,953.26, the system proves financially sound with an NPV of Rp. 4,380,435,791 and an IRR of 34.28%. Moreover, the installation significantly reduces carbon emissions by 2775.513 tons. This research underscores the practicality and environmental benefits of adopting solar energy in university campuses.